Performance of holstein calves from three to twelve months of age - Velazco, J.; Morrill, J. L.; Brandt, Robert T., Jr.; Schalles, R. (Kansas Agricultural Experiment Station, 2011)
Sixty-four Holstein steers were used to study the effect of season and age on performance. Animals beginning the trial in spring were heavier (P<.05) and more efficient than calves started in other seasons. There were no differences (P>.05) among seasons in average daily gain and feed conversion after 6 mo of age. Rate of growth was reduced after 9 mo of age for all seasons.
Keywords: Dairy; Calves; Growth; Seasons; Age